2013
DOI: 10.1063/1.4828437
|View full text |Cite
|
Sign up to set email alerts
|

Favorable adsorption of capped amino acids on graphene substrate driven by desolvation effect

Abstract: The use of graphene-based nanomaterials is being explored in the context of various biomedical applications. Here, we performed a molecular dynamics simulation of individual amino acids on graphene utilizing an empirical force field potential (Amber03). The accuracy of our force field method was verified by modeling the adsorption of amino acids on graphene in vacuum. These results are in excellent agreement with those calculated using ab initio methods. Our study shows that graphene exhibits bioactive propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
70
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(78 citation statements)
references
References 45 publications
7
70
1
Order By: Relevance
“…Previous studies using non-polarisbale FFs have shown a correlation between the enthalpy of adsorption and either the mass or hydrophilicity of the AAs. [39][40][41] The free-energies calculated here showed little correlation with either. While Arg, Gln, and Trp all possess large side-chains, Gly has the smallest sidechain of the set and yet also adsorbs strongly.…”
Section: Adsorption Free Energy Of Amino Acidsmentioning
confidence: 82%
See 4 more Smart Citations
“…Previous studies using non-polarisbale FFs have shown a correlation between the enthalpy of adsorption and either the mass or hydrophilicity of the AAs. [39][40][41] The free-energies calculated here showed little correlation with either. While Arg, Gln, and Trp all possess large side-chains, Gly has the smallest sidechain of the set and yet also adsorbs strongly.…”
Section: Adsorption Free Energy Of Amino Acidsmentioning
confidence: 82%
“…However, a number of previous studies have reported calculations of the adsorption enthalpy of AAs on graphene. [39][40][41]44 In these previous studies, Pandey et al used the, non-polarisable, AMBER ff99SB FF and calculated ∆H ads for capped AAs. While Camden et al calculated ∆H ads for G-X-G tripeptides (in the zwitterionic form) using the non-polarisbale TEAM FF.…”
Section: Adsorption Free Energy Of Amino Acidsmentioning
confidence: 99%
See 3 more Smart Citations